MANAGING PERSONAL FINANCE WIRED FOR WORK SOFT SKILL TRAINING BEKERJA SAMA DENGAN LSM â€œBULIR PADI FOUNDATIONâ€ DAN SMK PERTIWI - Sumani, Sumani; Dharmastuti, Christiana Fara (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The Bulir Padi Foundation, a non-profit organization that has been established since 2002, is committed to contributing to the education of underprivileged children in the suburbs of Jakarta by turning them into foster children. And in 2020, one of the work programs is to produce mentored children who have work skills so that the hope is that they are better prepared to enter the workforce at the entry level so that they can answer industry needs through providing job readiness training. To support the economic development of young people and the absorption of youth labor, The Wired For Work Soft Skill Training (W4W) program is a non-formal training program for Bulir Padi Foundation children to produce children who have work skills so that they are expected to be better prepared to enter the world of work at the entry level so that they can answer industry needs by providing readiness training. work. In this W4W Program, Bulir Padi Foundation will collaborate with Atma Jaya University and Pertiwi Vocational High School as a form of synergy between non-governmental organizations and the academic community in solving social problems, especially in the field of education. Pertiwi SMK students will be facilitated to receive soft skills training for their readiness to enter the world of work. The material covered in the Wired For Work Soft Skill Training (W4W) training activity this time includes Self management to improve work ethics, Implementing basic communications skills, Implementing the right equality of female and male workers in the workplace, Implementing the quality of grooming and professional manner, Preparing Job Application and interview test and Manage Personal Finances.